A Support Price Theorem for the Continuous Time Model of Capital Accumulation - Takekuma, Shin-Ichi (Econometrica, 1982)
We consider a model of capital accumulation and prove the existence of a support price path for the optimal path of capital accumulation. The considered model is a continuous time model of infinite horizon. Our problem is the so-called convex problem of optimal control without differentiability. We adopt the overtaking optimality criterion and prove the existence of a dual price path which supports the value function as well as the Hamiltonian function.